PARENTAL INVOLVEMENT ON CHILD’S EDUCATION AT HOME DURING SCHOOL LOCKDOWN - Lim Seong Pek; Rita Wong Mee Mee (UNIVERSITAS PAKUAN, 2020)
The pandemic of Covid-19 has changed how education works in the current time. A child’s learning development has always been placed on the responsibility of the school. However, during the pandemic, parental involvement has become vital in the world of education. The involvement of just a few parents may influence the quality of instruction in a classroom or at home and, thereby, influence the academic development of many children in Malaysia. This research aims to determine parental involvement child’s education in Selangor, Malaysia. Besides, it was also to help teachers and administrators to provide activities that encourage parents to participate in their child’s school activities at home. The data was collected via questionnaires and phone interviews. The participants involved were 10 parents and 5 teachers from a local primary school at the selected area during Movement Control Order (MCO). Based on the finding of this research, parental involvement has had a big influence in their child’s academic achievement. Although the importance of parental involvement is widely acknowledged in the educational society, most of parents showed that many parents still do not get involve effectively in their child’s education whether in school or at home. In conclusion, parental involvement is very essential in primary education and this will help to enhance child’s social relationships and promote a sense of self-esteem and self-efficacy